Gazebo Semar: An Android-based Farmer Education Platform for Agricultural Waste Management - Mahdaviqia Dharmawan; Lusia Dara Sari; Jericho Pandita Gunawan; Ernoiz Antriyandarti; An Duong (Universitas Ahmad Dahlan, 2023)
Agricultural waste and lack of knowledge about agricultural waste management is an environmental problem in Karanganyar Regency. Farmers in Karanganyar only handle agricultural waste, such as rice straws, husks, and corn stalks by burning them. Therefore, this study attempts to create innovation by educating farmers on properly treating agricultural waste. This study implemented mix method, namely application development and application evaluation by conducting survey. The Gazebo Semar application is built using a Kodular service begins with concept planning, interface design, features, and coding. Application evaluation were collected from a survey using a questionnaire of 120 farmers in Karanganyar Regency to evaluate the usability testing using USE (Usefulness, Satisfaction, and Ease to use) questionnaires and use the Likert scale for measurement. Gazebo Semar is a solution to provide information on agricultural waste types, waste management, and marketing of processed agricultural waste products. This application allows the users to easily access information about agricultural waste and Zero Waste without visiting multiple websites or blogs. The Gazebo Semar App has nine main features: Home Screen, Zero Waste, SDGs, Waste Source, Waste Classification, Waste Management, Gazebo Semar Store, Quiz, and About Us. Gazebo Semar provides a number of novelties in terms of substance and features, so that it is expected to have an impact on local farmers especially in the field of agricultural waste processing. The results show that the score of Usefulness, Satisfaction, and Ease of Use is above 71%, which means Gazebo Semar has provided the application that fits with the needs of farmers. The research contribution is to improve the mindset of farmers in processing agricultural waste into other forms that are more economically valuable. The significance of this study is to increase public knowledge about agricultural waste, zero waste, and waste management.